THE ANALYSIS OF STUDENTS’ DIFFICULTIES IN READING DESCRIPTIVE TEXT AT THE EIGHTH GRADERS OF SMP MUHAMMADIYAH PAGARALAM - Umi Kalsum (STKIPM PRESS, 2022)
ABSTRCT This study aims to analyze the difficulties of students in reading descriptive texts in class VIII SMP Muhammadiyah Pagaralam. This study used a qualitative descriptive method to analyze the data. The population of this study were students of class VIII SMP Muhammadiyah Pagaralam, and the sample was taken by purposive sampling technique. The data of this research is the students’ difficulties in reading descriptive text. Data were collected using interviews and questionnaires. To find out the results of the data that has been given to students , the author uses the percentage formula. The results showed that the difficulties in reading descriptive text was low. It can be seen from the data, they still have difficulties in reading descriptive texts. Regarding the results, the writer suggests that students practice their reading skills specifically in descriptive texts. If they practice more, they will have good reading skills. To the English teacher, the writer suggests giving more explanations and exercises for students related to descriptive texts. Then for other researchers, the writer suggests studying students’ difficulties in reading descriptive texts.